ETOS KERJA DALAM KERANGKA PEMIKIRAN HASBI ASH SHIDDIQY DAN A.HASSAN - Maisarotil Husna (Hadharah: Jurnal Keislaman dan Peradaban, 2018)
Work ethics include not only how one feels about their job, career or vocation, but also how one does his/her job or responsibilities. This involvesattitude, behavior, respect, communication, and interaction; how one getsalong with others. Therefore, work ethics demonstrate many things aboutwhom and how a person is. This study was conducted with the purpose ofexploring the view of Hasbi Ash Siddiqy and A. Hassan regarding workethics. Descriptive and analytic studies were used as a focus on their work,especially on their commentary in the Tafsir Annur and Tafsir al-furqan. Thispaper analyzed the verses of work ethics in the Holy Qur'an and how tounderstand the verses of work ethics in their interpretation by usingcomparative method. The results of this study demonstrate that Hassan andHasbi interpret the work ethic as a desire or determination to work hard inwhich is based on the intention of worship to fight for the welfare of theHereafter